The association of accelerometer‐measured physical activity, white matter hyperintensity volume, and cognition in normal aging. (20th December 2022) - Calcetas, Amanda T.; Bangen, Katherine J.; Thomas, Kelsey R.; Smith, Christine N.; Bordyug, Maria; Brenner, Einat K; Zlatar, Zvinka
Abstract: Background: White matter hyperintensities (WMH) are an indicator of small vessel cerebrovascular disease, which increases the risk of developing Alzheimer's disease and related dementia (ADRD). Moderate to vigorous intensity physical activity (MVPA), can help maintain brain structure, function, and cognition in aging. However, the mechanisms by which MVPA may preserve cerebrovascular health remain understudied. To help elucidate the cerebrovascular mechanisms by which MVPA preserves cognition, we examined associations of MVPA and WMH volume, MRI markers of neurodegeneration, and cognition. Method: Forty‐three adults without cognitive impairment (aged 65–85, 74% female) were recruited from ongoing studies at the University of California, San Diego and underwent MRI exams and comprehensive neuropsychological assessment. Waist‐worn accelerometers objectively measured MVPA for one week. WMH volume was quantified on fluid‐attenuated inversion recovery (FLAIR) scans using semi‐automated procedures and were log transformed and normalized by total intracranial volume (ICV). Hippocampal volume (normalized by ICV) and entorhinal thickness were derived via FreeSurfer. Adjusting for age, sex, and education, ANCOVA models compared participants who had <60 minutes of MVPA per week (n = 18; MVPA<60 group) to those who had ≥60 minutes of MVPA per week (n = 25; MVPA≥60 group) on MRI markers of WMH, hippocampal volume, and entorhinal thickness, and neuropsychological performance on measures of executive function, language, and memory. Result: Older adults in the MVPA≥60 group had lower WMH volume compared to those in the MVPA<60 group (p = 0.036, ηp 2 = 0.108). There were no significant differences in hippocampal volume (p = 0.157, ηp 2 = 0.052) or entorhinal thickness (p = 0.980, ηp 2  = 0.000) between MVPA groups. The MVPA≥60 group performed better on measures of executive function (Trails B, p = 0.030, ηp 2 = 0.109) and language (category fluency, p = 0.030, ηp 2 = 0.110) than the MVPA<60 group, although the groups did not differ on memory performance (p's >.05). Conclusion: Engaging in 60+ minutes of MVPA week may be beneficial for cerebrovascular health and help preserve some aspects of executive and language function performance in older adults. Future work will determine whether better cognitive performance in the MVPA≥60 group is mediated by lower WMH volume. Furthermore, randomized controlled trials that increase MVPA are needed to elucidate cause‐effect associations between MVPA and cognitive and brain health.